Whatsapp Group Sebagai Digital Heterotopia: Dari Sumber Informasi Digital Hingga Digital Leisure - Sugihartati, Rahma; Egalita, Nadia; Wijaya, Arya (Jurnal Ilmu Informasi, Perpustakaan, dan Kearsipan, 2021)
This article reports the study of the use of WhatsApp Group (WAG) among primary school students who utilize the platform as a digital heterotopia. The study investigated: How is WAG used as a platform for sharing and exchanging YouTube content among primary school students?; How WAG is represented as a digital space for during their practices of sharing and exchanging YouTube content? The purpose of this research is to explore information dissemination activities, especially YouTube content WAG as a digital space for information sharing has become a heterotopia digital space. This qualitative research was conducted in Surabaya, Malang, Kediri, and Jember. Data was collected from indepth interview of 50 primary school students. This study found that firstly, the students do not only use their WAG to disseminate YouTube content for academic purposes, but also to turn WAG as a space of digital leisure. Children as the iGeneration immerse themselves into the cyberspace to interesting videos on YouTube, as well as game-related content which they share to their friends through WAG. Secondly, the existence of WAG for these students does not only serve as a space for educational purposes – exchanging academic content, but also as a space for social interaction, self-representation and con-structing self-identity. WAG among primary school students is a digital heterotopia as they can use it as a space for sharing and exchanging various YouTube content for their social loop, and social validation from their digital peers.